Diagnostic study of the green alga Dunaliella salina in the brine ponds from Basrah Governorate and the effect of chloride salt on alga growth and carotene production. - AL-Sultan, Emad Y.A.; Abdulla, Anfal F. (Iraqi Journal of Aquaculture, 2023)
The current study included shedding light on one genus of green alga Dunaliella salina spread from the saline brine ponds, Basrah Governorate, southern Iraq. Morphological results showed all algal samples from different brine ponds sites in Basrah governorate were belong to the species D. salina, and the measured enviro-nmental factors are commensurate with the growth of this species especially salinity, due to its increasing growth compatible increasing salinity with significantly P≤0.05 at concentrations 0-15% of sodium chloride salt, which equaled a salinity level more than 4 times the salinity of sea water, which amounted to 150 g/L. finding showed the concentration 5% of sodium chloride is considered it is a suitable concentration for the growth of all alga samples with no significant differences P≤0.05 between the generation time (G) and constant growth (K) for all cultures samples. Finding was proven that all isolates of the different sites showed the ability to produce total carotene in response to an increase or decrease in salinity, as is the case in the salinity-free control group as an effort that requires the alga to produce carotene, and this is an important characteristic for this species as well. From these results, it can be concluded that all isolates of algae from different sites belong to only one species diagnosed in the current study.